Age-related changes in the BACH2 and PRDM1 genes in lymphocytes from healthy donors and chronic lymphocytic leukemia patients - Vu Luan Dang Chi; Soizic Garaud; Pushpamali De Silva; Vincent Thibaud; Basile Stamatopoulos; Mimoune Berehad; Chunyan Gu-Trantien; Mohammad Krayem; Hugues Duvillier; Jean-Nicolas Lodewyckx; Karen Willard-Gallo; Catherine Sibille; et al. (BMC Cancer, 2019)
Abstract Background Age-related genetic changes in lymphocyte subsets are not currently well documented. BACH2 is a transcription factor that plays an important role in immune-mediated homeostasis by tightly regulating PRDM1 expression in both B-cells and T-cells. BACH2 gene expression is highly sensitive to DNA damage in aged mice. This concept led us to investigate the variation in BACH2 and also PRDM1 expression in major lymphocyte subsets with age. Methods Lymphocyte subsets from 60 healthy donors, aged from 20 to 90 years, and 41 untreated chronic lymphocytic leukemia patients were studied. BACH2 and PRDM1 gene expression was analyzed by real-time quantitative PCR. BACH2 gene expression was correlated with its protein expression. Lymphocyte apoptosis was evaluated after intracellular oxidative stress-inducing etoposide treatment of T and B cells. Results Our analysis shows BACH2 mRNA downregulation with age in healthy donor CD4+, CD8+ T-cells and CD19+ B-cells. Decreased BACH2 expression was also correlated with an age-related reduction in CD8 + CD28+ T-cells. We found a strong correlation between age-related BACH2 downregulation and decreased CD4+ T-cell and CD19+ B-cell apoptosis. PRDM1, as expected, was significantly upregulated in CD4+ T-cells, CD8+ T-cells and CD19+ B-cells, and inversely correlated with BACH2. A comparison of untreated chronic lymphocytic leukemia patients with age-matched healthy donors reveals that BACH2 mRNA expression was further reduced in CD4+ T-cells, CD8+ T-cells and leukemic-B cells. PRDM1 gene expression was consequently significantly upregulated in CD4+ and CD8+ T-cells in chronic lymphocytic leukemia patients but not in their leukemic B-cells. Conclusion Overall, our data suggest that BACH2 and PRDM1 genes are significantly correlated with age in human immune cells and may be involved in immunosenescence.